USE OF TECHNIQUE OF REPERTUARY GRILLES IN THE FORMATION OF INTERPERSONAL RELATIONSHIPS OF JUNIOR SCHOOLCHILDREN - Miroshnyk, Z.M.; Mykhaylenko, O.Yu. (Pedagogy of Higher and Secondary Education, 2022)
This article is an attempt to build individual space for younger pupils using the technology of repertory grids.